Association of plasma brain-derived neurotrophic factor with Alzheimer’s disease and its influencing factors in Chinese elderly population - Qian, Fuqiang; Liu, Jian; Yang, Hongyu; Zhu, Haohao; Wang, Zhiqiang; Wu, Yue; Cheng, Zaohuo (Frontiers in Aging Neuroscience, 2022)
Objective: To explore the association of plasma BDNF levels with Alzheimer's disease and its influencing factors. Methods: A total of 1615 participants were included in the present study. Among all subjects, 660 were cognitive normal controls (CNCs), 571 were mild cognitive impairment (MCI) patients, and 384 were dementia with Alzheimer's type (DAT) patients. BDNF in blood samples collected from these subjects was analyzed via the Luminex assay. Additionally, DNA extraction and APOE4 genotyping were performed on leukocytes using a blood genotyping DNA extraction kit. All data were processed with SPSS 20.0 software. Analysis of variance (ANOVA) or analysis of covariance (ANCOVA) was used to compare differences among groups on plasma BDNF. Pearson and Spearman correlation analysis examined the correlation between BDNF and cognitive impairment, and linear regression analysis examined the comprehensive effects of diagnosis, gender, age, education and sample source on BDNF. Results: BDNF levels in DAT patients were higher than those in CNC and MCI patients (P<0.01). BDNF levels were significantly correlated with CDR, MMSE, and clinical diagnosis (P<0.001). Age, education, occupation and sample source had significant effects on BDNF differences among the CNC, MCI and DAT groups (P<0.001). BDNF first decreased and then increased with cognitive impairment in the ApoE4-negative group (P<0.05). Conclusion: Plasma BDNF levels decreased in the MCI stage and increased in the dementia stage and were affected by age, education, occupation and sample source. Unless the effects of sample heterogeneity and methodological differences can be excluded, plasma BDNF is difficult to become a biomarker for the early screening and diagnosis of AD.